If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (y + -9) + -1(Y + 8) = 6y Reorder the terms: (-9 + y) + -1(Y + 8) = 6y Remove parenthesis around (-9 + y) -9 + y + -1(Y + 8) = 6y Reorder the terms: -9 + y + -1(8 + Y) = 6y -9 + y + (8 * -1 + Y * -1) = 6y -9 + y + (-8 + -1Y) = 6y Reorder the terms: -9 + -8 + -1Y + y = 6y Combine like terms: -9 + -8 = -17 -17 + -1Y + y = 6y Solving -17 + -1Y + y = 6y Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '17' to each side of the equation. -17 + -1Y + 17 + y = 17 + 6y Reorder the terms: -17 + 17 + -1Y + y = 17 + 6y Combine like terms: -17 + 17 = 0 0 + -1Y + y = 17 + 6y -1Y + y = 17 + 6y Add '-1y' to each side of the equation. -1Y + y + -1y = 17 + 6y + -1y Combine like terms: y + -1y = 0 -1Y + 0 = 17 + 6y + -1y -1Y = 17 + 6y + -1y Combine like terms: 6y + -1y = 5y -1Y = 17 + 5y Divide each side by '-1'. Y = -17 + -5y Simplifying Y = -17 + -5y
| 3x^2-130x-5600=0 | | x-0.4x=107820 | | x^2=-242 | | 7x-2y=32 | | x^4-4x^3+x^2+4x+1=0 | | 8t=51 | | x^2+0.2x-0.24=0 | | Y=x+6x+10 | | -6 x+ 4 y= 12 | | a+a+1+a+2+a+3=34 | | X^3+7x^2+10x-6=0 | | 3=2+2b | | 3x^2+22x-2600=0 | | Y=x^2-14x-59 | | 7+4x=3y | | 5g-6-4-5g= | | -16t^2+2304=0 | | -16t+2304=0 | | 3w/2w-6 | | 4(2x+5)=3(5x-6) | | 4x^2+13x=0 | | (2x+3)(x-1)+(3x-5)(2x+7)=0 | | 9x^2-2X=5 | | -5(5r+9)+5(r-6)= | | 12=3600/r | | 55-x=-12 | | x+5y+2x+2y+3=90 | | 3872=1/2m22 | | 2Ix^2*1=10x | | -16t+64t+960=0 | | -mx+y+2=0 | | r^2+(r^2+4r+4)-74=0 |